The Effect of Applying the Outdoor Learning Method on Student Learning Motivation in the Museology Course, History Education Study Program, IKIP PGRI PONTIANAK - Bahri, Saiful; Januardi, Arif (Jurnal Pendidikan Ilmu Sosial, 2021)
The purpose of this study was to see the effect of the outdoor learning method on student motivation in the Museology course of the History Education Study Program at the IKIP PGRI Pontianak. This research method used is experimental, with a research design that is Quasi experimental. The experimental class is A and the control class is B. The location is on the IKIP PGRI Pontianak campus. Data collection techniques with learning motivation questionnaires, observation sheets and documentation. Data analysis techniques used descriptive statistics, parametric statistical tests, and used the Effect Size formula. The results of this study are 1. The average learning motivation of students who are not taught using the History Education laboratory is 66.33 which is classified as sufficient. 2. The average learning motivation of students who are taught or the experimental class using the outdoor learning method is 77.42 which is classified as good. 3. There is a significant difference in the average learning motivation of students in the control class and students in the experimental class. 4. Based on the calculation using the effect size obtained Es 80, or Es = 0.55, it can be concluded that the use of the outdoor learning method on learning motivation in Museology courses is classified as moderate.